PEMETAAN DATA RECHARGE AIR TANAH DI KABUPATEN SLEMAN BERDASARKAN DATA CURAH HUJAN - Bambang Yuwono; Awang Hendrianto Pratomo; Heru Cahya Rustamaji; Puji Pratiknyo; Mochammad Assofa Indera Jati (Jurusan Teknik Informatika, 2016)
Water is a basic need for humans and other living things. Various sources of water on this earth has formed a system of close interaction with the components of living things in it. Over the years, water resources have changed in terms of both quality and quantity. This can be due to population growth in addition to the natural changes in nature. The more narrow field of water absorption followed by high water consumption causes the supply of ground water reserves can be threatened. So, we need a mapping and ground water recharge calculations to assist in the monitoring of groundwater reserves.The method used in this research is the Water Balance (keseimbangan air)method. This method is based on any incoming rain water will be equal to the output evapotranspiration and runoff hereinafter this method is applied in the application. Factors affecting groundwater recharge the water balance method is precipitation, evapotranspiration and run off. Information og groundwater recharge is also displayed on the map using Google Map function are related to the database system to produce informative mapsCalculation of groundwater recharge is applied to the daily rainfall data input into the application which then included in the water balance equation method so it can be easy to determine the value of groundwater recharge. Groundwater recharge information can be displayed in the form of mapping, making them easier to understand visually.Based on testing, the highest recharge results of this research on the Kemput station is 1119,5 mm/year with rainfall of 2750 mm/year. Seyegan and Bronggang station is 1026,25 mm/year with rainfall of 2625 mm/year. Angin-angin and Prumpung station is 933 mm/year with rainfall of 2500 mm/year. Beran and Gemawang station is 839.5 mm/year with rainfall of 2375 mm/year. Plataran station is 808.42 mm/year with rainfall of 2333 mm/year. Godean station is 699.5 mm/year with rainfall of 2187 mm/year and the lowest at Tirto Tanjungand Santan stastion 560 mm / year with rainfall of 2000 mm / year.